Assessing Instructional Leadership with the Principal Instructional Management Rating Scale - Hallinger, Philip. author. aut Link
XVII, 204 p. 13 illus.
Keywords: This volume provides a succinct up-to-date summary of global research on principal instructional leadership as it has evolved over the past 50 years. The book’s particular focus is on the development and use of the Principal Instructional Management Rating Scale (PIMRS). The PIMRS is the most widely used survey instrument designed for assessing instructional leadership for research and practice. It has been used in more than 250 studies in more than 30 countries around the world. The authors provide a detailed conceptual and data-based description of the rationale and development of the instrument as well as the ways in which it has been used in practice. The book also provides, for the first time, a comprehensive assessment of the scale’s measurement properties. This represents essential information for future users of the instrument across different national contexts. Finally, the volume outlines an agenda for improving future research on the role of principal instructional leadership in student learning and school effectiveness.